2021
DOI: 10.1177/10901981211053247
|View full text |Cite
|
Sign up to set email alerts
|

“I Can’t Go Far”: Perceptions and Experiences of Heart Failure Patients Regarding Physical Activity: A Qualitative Study Using Semistructured Face-to-Face Interviews

Abstract: Background Participation in regular physical activity (RPA) is beneficial to the quality of life and life expectancy of patients with chronic heart failure (CHF). However, it is inadequate in many patients. Aims To determine the factors that influence the practice of RPA in patients with CHF managed in general practice. Method This was a qualitative study using semistructured, individual face-to-face interviews. Patients with CHF (New York Heart Association Stages 1–3) capable of participating in RPA were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Several studies showed that patients with HF experienced fear, social isolation, and loss of control, which could lead to psychological distress, depression, anxiety, and frustration. [ 23 24 ] Several other studies have reported the relationship between psychological distress and poor self-care behaviors. [ 25 26 ] Heo et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed that patients with HF experienced fear, social isolation, and loss of control, which could lead to psychological distress, depression, anxiety, and frustration. [ 23 24 ] Several other studies have reported the relationship between psychological distress and poor self-care behaviors. [ 25 26 ] Heo et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, support should not be so great that patients become passive in their care and dependent on others. [ 23 ] Perceived emotional/informational support is associated with better self-care management. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some specific examples include facilitating communication between patient and provider, appointment reminders, assisting with medication refills, providing educational resources, and providing emotional support [ 3 ]. These services, among others, have been shown to increase patient understanding of their disease and lead to improved patient outcomes [ 4 15 ]. The most robust data demonstrating the efficacy of PN programs comes from improving cancer screening and treatment [ 16 ], various primary care interventions [ 5 , 9 ], and HIV medication adherence [ 10 ].…”
Section: Introductionmentioning
confidence: 99%